Use of GeoGebra in Primary Math Education in Lithuania: An Exploratory Study from Teachers' Perspective - Demirbilek, Muhammet; Žilinskienė, Inga (Informatics in education, 2015)
With the advance of information and communications technologies, new teaching tools are becoming more pervasive. These tools can be utilized in a variety of ways to improve and enhance math teaching. Considering the integration of technology in teaching mathematics, it is clear that the replacement of board and chalk with digital presentation material does not cover all the aspects of the mathematic subjects. One of the important prerequisites for quality of integration technology into mathematics teaching is the teacher’s personality, i.e. knowledge, willingness and desire to improve his/her lessons bringing mathematics closer to the present generations of pupils. GeoGebra as a dynamic mathematics software allows users to explore multiple representations of mathematics concepts. The paper deals with the problem of deployment of GeoGebra in Lithuanian’s primary math education and the main purpose of this study is to investigate reasons/factors affecting teachers’ decision to utilize GeoGebra and learning objects prepared by it in their teaching process. With a view to evaluate GeoGebra’s suitability to primary education an expert opinion poll was conducted and results of that exploratory study are presented.